15 Answers | Add Yours
As written, the expression (x + 3)(x + 9) is not an equation, so there is nothing to solve. This expression may be simplified by multiplying through the parenthesis.
(x + 3)(x + 9) = (x + 3)*x + (x + 3)*9
= x^2 + 3x + 9x + 3*9
= x^2 + 12x + 27
Often expressions such as that given are set equal to zero, in which case there is an equation.
(x + 3)(x + 9) = 0 may be solved by remembering that if a*b = 0, then either a or b must be equal to zero. Thus either x + 3 = 0 or x + 9 = 0, meaning that x = -3 or x = -9
To solve this equation, we can use FOIL -- First, Outside, Inside, Last
Use the foil method and distribute the first x and the 3 to the other numbers.
The answer is x^2+12x+27
(x+3)×(x+9). You have to take one part I.e. X and then multiply it to the entire second equation I.e. x+9. And then put the same sign as in the middle in this case it's addition and then repeat the first step but multiply by 3 so you get something like this X squared + 9x + 3x + 27. Then simplify to x^2 +12x+27.
For (x+3)(x+9) you have to use FOIL
Combine Like Terms
I am assuming the problem is this:
(x+3)(x+9) = 0
We know that either
x + 3 = 0 or x + 9 = 0
Solve for the two different x values independently and get:
x = -3 x = -9
Depending on the real life application (if there is one for this problem) one of the answers is extraneous.
use the foil method, multiply every number in the first parentheses by every number in the second parentheses:
`x xx x=x^2 `
`x xx 9=9x `
combine like terms which would be `9x+3x=12x`
x^2 + 12x + 27
These questions are made into equations so you can solve them. The key is to make both sides of the equation equal. I call it balancing the scale.
Start with (x+3)(x+9)=0
Then FOIL Method
We’ve answered 317,653 questions. We can answer yours, too.Ask a question